PEMBELAJARAN UNIK PADA ANAK YANG MEMILIKI KECERDASAN VISUAL SPASIAL YANG MENGALAMI KESULITAN BELAJAR - Ulwan Syafrudin; Edwita Edwita; Sarkadi Sarkadi (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2018)
This research is motivated by students who have learning difficulties but have advantages of spatial visual intelligence which has been proven byquestionnaire multiple intelligence. So the purpose of this study to describe how students learn who have spatial visual intelligence who have learning difficulties. This research was conducted at SDIT Harapan Ummat located at Jalan Ksatrian X sub district of Matraman East Jakarta. researchers conducted a study on one of the students in class IV B Muzdalifah in the period of March to June 2018. The research method used in this research is descriptive method, descriptive method is a method of research that seeks to describe and interpret the object in accordance with what it is. Based on the findings of Learning in children who have spatial visual intelligence at SDIT Harapan Ummat Jakarta using the curriculum 2013 but adapted to the ability and disability of children with attention to the differentiation of each individual. In the implementation of this learning includes several stages: (1) Initial Activities, (2) Core Activities, (3) Final Activity. In this research, it can be concluded that teacher strategy in teaching to students who have learning difficulties that have spatial visual intelligence are Mind Mapp and Movie Learning.